KORELASI PERSEPSI SISWA TERHADAP LAYANAN KONSELING INDIVIDUAL DENGAN MINAT BERKONSELING PADA SISWA SMK PGRI WONOASRI KABUPATEN MADIUN TAHUN PELAJARAN 2017/2018 - Mudjijanti, Fransisca (Widya Warta, 2020)
The  purpose  of  this  study  was  to  obtain  an  description  on  students'  perceptions  towards individual  counseling  services  and  students'  counseling  interests  and  then  to  analyze whether there was a correlation between students' perceptions towards individual counseling services with counseling interests on the students of SMK PGRI Wonoasri Madiun Regency in  2017/2018  Academic  Year,  using  cluster  random  sampling  obtained  from  118  students. The description of students' perceptions towards individual counseling services is positive in the very high category and students' counseling interests are generally in the high category. The  research  hypothesis  "Students'  perceptions  towards  individual  counseling  services correlate  with  students'  counseling  interests  of  SMK  PGRI  Wonoasri  Madiun  Regency  in 2017/2018" is proven.